2017
DOI: 10.1158/1055-9965.epi-16-0948
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trimethylamine N-oxide, Carnitine, Choline, and Betaine in Relation to Colorectal Cancer Risk in the Alpha Tocopherol, Beta Carotene Cancer Prevention Study

Abstract: Background TMAO, a choline-derived metabolite produced by gut microbiota, and its biomarker precursors have not been adequately evaluated in relation to colorectal cancer risk. Methods We investigated the relationship between serum concentrations of TMAO and its biomarker precursors (choline, carnitine and betaine) and incident colorectal cancer risk in a nested case-control study of male smokers in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Study. We measured biomarker concentrations in ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 36 publications
1
60
2
Order By: Relevance
“…14 Prospective studies have reported that a high level of circulating choline is associated with an increased risk of colorectal cancer. 15,16 Phosphatidylcholines can also be synthesized in the liver via the phosphatidylethanolamine methylation pathways. 14,17 Phosphatidylethanolamines are derived from cytidine diphosphate ethanolamines, which are downstream derivatives of ethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…14 Prospective studies have reported that a high level of circulating choline is associated with an increased risk of colorectal cancer. 15,16 Phosphatidylcholines can also be synthesized in the liver via the phosphatidylethanolamine methylation pathways. 14,17 Phosphatidylethanolamines are derived from cytidine diphosphate ethanolamines, which are downstream derivatives of ethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between serum concentrations of TMAO and its precursors (choline, carnitine and betaine) and incident colorectal cancer risk was also investigated in a nested case–control study of male smokers in the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention (ATBC) Study (Guertin et al., ). Men with higher serum choline at baseline had approximately threefold greater risk of developing colorectal cancer over the ensuing 14 ± 10 years while the association between serum TMAO, carnitine or betaine and colorectal cancer risk was not statistically significant.…”
Section: Assessmentmentioning
confidence: 99%
“…H 2 O 2 ‐induced oxidative cellular damage of K562 cells could be prevented when treated with BC (Akçakaya, Tok, Dal, Cinar, & Nurten, 2017). BC is known to prevent the cardiovascular diseases and various cancers in human (Guertin et al, 2017; Voutilainen, Nurmi, Mursu, & Rissanen, 2006). BC is soluble in fats but insoluble in aqueous medium and its solubility in oil is inversely proportional with fatty acid length (Borel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%